Quality of Work Life and Work Environment on Organizational Citizenship Behavior with Job Satisfaction as Mediation - MH Thamrin, Rosiyati; Rahmawati, Rini; Rusmin Nuryadin, Muhammad; Juniar, Asrid (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aims to analyze the influence of the quality of work life and work environment on organizational citizenship behavior (OCB) with job satisfaction as mediation in the state civil apparatus in Hulu Sungai Selatan district. The population in this study was 15,017 people with a sample of 220 people in government agencies. The sampling technique used purposive sampling with the criteria of employees having a structural position of more than 3 years. This type of research is quantitative and data collection uses a questionnaire. The data analysis technique used in this study is Structural Equation Modeling (SEM). The novelty of this research is that the object of research is government employees, so it is different from previous research conducted on non-government employees. The results of this study indicate that the quality of work life and work environment have a significant effect on organizational citizenship behavior (OCB) with job satisfaction as mediation. Employees who are satisfied with what they have done are supported by a good work environment and quality of work life will be able to create organizational citizenship behavior (OCB), namely doing work outside their job description according to the job description without having to be forced or coerced. do it voluntarily.